The Effect of Customers Engagement and Electronic Word of Mouth n Purchase Decision Through Purchase Intention as a Mediation Variable: (Case Study on Tomoro Coffee) - Indah Dwi Lestari; Novita Fitri Yanti Seragih; Moh Reza Munandar; Firdaus Rofiansyah; Rahmawati Rahmawati (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of customer engagement and electronic word of mouth (eWOM) on purchase decisions mediated by purchase intention among Tomoro Kopi consumers. The Structural Equation Modeling (SEM) approach with the Partial Least Square (PLS) method was used to test the relationship between variables. The sample used in this study was 80 respondents in Samarinda City. The results showed that customer engagement has a positive and significant effect on both purchase intention and purchase decision, indicating that the higher the level of customer engagement, the stronger the purchase intention and resulting purchase decision. Conversely, electronic word of mouth does not have a direct effect on purchase decisions, but has an indirect effect through purchase intention. This finding confirms that eWOM can only drive purchase decisions if it first increases consumer purchase intention. In addition, purchase intention has been proven to have a significant effect on purchase decisions, making purchase intention a key factor that bridges the consumer's psychological process before making an actual purchase.